Channel management 2 - Dent, Julian (Henry Stewart Talks, 2012)
Reach and coverage, Channel resources/players, Channel requirements, Channel programmes, Business models, Engaging the channel, Channel value proposition, Recruiting partners, Account management, Development plans, Measuring performance, Performance analysis, Cost to sell, Cost to serve, Return on marketing